Crystal and molecular structures of two triazole derivatives: 4-Cyclopropyl-4,5-dihydro-1H-1,2,3-triazole and Methyl 1-benzyl-1H-1,2,3-triazole-4-carboxylate - Boechat, N.; Ferreira, M.D.L.G.; Bastos, M.M.; Camilo, A.L.S.; Wardell, S.M.S.V.; Wardell, J.L.; Tiekink, E.R.T. (Kluwer (now part of Springer), 2010)
The molecule in 4-cyclopropyl-4,5-dihydro-1H-1,2,3-triazole (I) is disposed about a mirror plane with the triazole ring lying in the plane and being orthogonal to the cyclopropyl ring. Considerable delocalization of pi-electron density within the triazole ring is indicated by the pattern of bond distances in (I). The molecule of methyl 1-benzyl-1H-1,2,3-triazole-4-carboxylate (II) adopts a curved shape with the dihedral angle formed between the triazole and benzene rings being 63.23(8)A degrees. By contrast to (I), localization of pi-electron density within the triazole ring in (II) is indicated. Both (I), via N-H center dot center dot center dot N hydrogen bonding, and (II), via C-H center dot center dot center dot O and C-H center dot center dot center dot N interactions, associate in the solid state to form supramolecular chains. In (I), the chain is a zigzag with a flat topology, whereas in (II) the linear chain has a curved topology. Compound (I) crystallizes in the orthorhombic space group Pnma with a = 5.6470(2) angstrom, b = 7.3359(4) angstrom, c = 13.4404(7) angstrom, and Z = 4. Compound (II) crystallizes in the monoclinic space group P2(1)/c with a = 12.1314(5) angstrom, b = 5.5951(2) angstrom, c = 16.4339(7) angstrom, beta = 111.269(2)degrees, and Z = 4.